Queering lesbian, gay, bisexual and transgender identities in human resource development and management education contexts. Issue 2 (April 2017) - Rumens, Nick
Taking human resource development as its primary context, this article asks, 'How can scholars mobilise queer theory concepts to move beyond treating lesbian, gay, bisexual and transgender identities as binaried, bounded and stable categories?' While human resource development scholarship has made important, albeit limited, progress here, this article provides a review of queer theory to help scholars engage more deeply with some of its key concepts and theoretical resources to that end. In particular, one of this article's main contributions is advancing the nascent in-roads Judith Butler's writing has made into human resource development, management education and learning by linking her theory of gender performativity with the notion of cultural intelligibility. The aim of the article is to show how lesbian, gay, bisexual and transgender identity categories can be destabilised so that they can be examined queerly: performatively constituted and permanently open to contestation and resignification. Crucially, the wider applications and implications of queer theory are drawn out, such as how queer pedagogy can inform management education. This article also highlights possibilities for management learning scholars to queer other identities (e.g. heterosexual), organisations and modes of organising.